If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 1)(6 + -2x) = x(4 + -8x) Reorder the terms: (1 + 4x)(6 + -2x) = x(4 + -8x) Multiply (1 + 4x) * (6 + -2x) (1(6 + -2x) + 4x * (6 + -2x)) = x(4 + -8x) ((6 * 1 + -2x * 1) + 4x * (6 + -2x)) = x(4 + -8x) ((6 + -2x) + 4x * (6 + -2x)) = x(4 + -8x) (6 + -2x + (6 * 4x + -2x * 4x)) = x(4 + -8x) (6 + -2x + (24x + -8x2)) = x(4 + -8x) Combine like terms: -2x + 24x = 22x (6 + 22x + -8x2) = x(4 + -8x) 6 + 22x + -8x2 = (4 * x + -8x * x) 6 + 22x + -8x2 = (4x + -8x2) Add '8x2' to each side of the equation. 6 + 22x + -8x2 + 8x2 = 4x + -8x2 + 8x2 Combine like terms: -8x2 + 8x2 = 0 6 + 22x + 0 = 4x + -8x2 + 8x2 6 + 22x = 4x + -8x2 + 8x2 Combine like terms: -8x2 + 8x2 = 0 6 + 22x = 4x + 0 6 + 22x = 4x Solving 6 + 22x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 22x + -4x = 4x + -4x Combine like terms: 22x + -4x = 18x 6 + 18x = 4x + -4x Combine like terms: 4x + -4x = 0 6 + 18x = 0 Add '-6' to each side of the equation. 6 + -6 + 18x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 18x = 0 + -6 18x = 0 + -6 Combine like terms: 0 + -6 = -6 18x = -6 Divide each side by '18'. x = -0.3333333333 Simplifying x = -0.3333333333
| 3x+33=10x-51 | | -9v-8=12 | | -10=9v-1 | | -8x+7y=-56 | | 0.8+9.9=6.3 | | -3z+1=-17 | | 0=4w-28 | | 3(x+4)=22-x | | (3x-3x)4x=2 | | 0=2w-16 | | 4x-3=10-x | | 5*2.6=r | | 5-3y=19 | | 0=-4x-7 | | (x-2)(x-3)=0 | | 14-3a=4 | | 7-3x=3x-2 | | -2x++4=5-3x | | -8x+7*0=-56 | | 12-2x=3x+4 | | 10-3x=3x-2 | | 3x-7=13-2x | | 9x-2=28-x | | .5x+6=.33x | | 9x-2=28-2 | | 14(t-6)+4t=6(3t+5)-12 | | -8x+7-0=-56 | | 5z=-3(z+8) | | 3x+9=7x-9 | | -1[a-1(a+-5)]+-3=-5-1(-9+-5) | | 5c=-3(2+8) | | 12(3x+6)-7(2x-6)=2x-26 |